Mask associated dermatosis: unmasking the challenges- a cross sectional study - ., Ketki; Gupta, Sonali; Paliwal, Vijay; Mathur, Rachita; Mathur, Deepak K. (International Journal of Research in Dermatology, 2021)
Background: The novel coronavirus, referred to as SARS-COV 2 causing COVID 19, has become a great health challenge to the mankind. After its origin from Wuhan, China, it spread all over the globe within a short period of time. World Health Organization (WHO) officially declared COVID 19 as pandemic on 11th March, 2020. Aerosoles or droplets are the commonest mode of infection through respiratory tract making it mandatory to wear masks as a preventive measure. Methods: It is a cross-sectional study conducted over patients attending the out patients department of Dermatology. They were observed for presence of dermatosis over the face and categorized according to nature of dermatoses. Results: We observed 385 patients, 200 (52%) patients had new dermatoses and 185 (48%) patients noticed flare of existing dermatoses. The predominant new dermatoses were dermatophytosis, indentations, sweat induced dermatitis, urticaria, pressure urticaria developing with indentations, contact dermatitis to metal and other materials in 49 (24.5%%), 42 (21%), 42 (21%) ,38(19%), 19 (9.5%) and 10 (5%) cases respectively. The flared dermatoses were acne, rosacea , plane warts and molluscum contagiosum in 120 (64.8%), 24 (12.9%), 22 (11.9%) and 17 (9.2%) cases respectively. Koebnerisation of vitiligo and lichen planus was also seen in few subjects. Conclusions: The prolonged use of face mask may cause various infective and non infective facial dermatoses. In the current scenario, it is mandatory to wear face mask as a preventive measure hence it is important to wear the mask properly. However, care of the mask as well as breaks from the mask are important factors to avoid the development of mask associated dermatosis.